Development and Shelf Life of Traditional Ladcheag Products in the Three Southern Border Provinces of Thailand - เจะดอเลาะ รอมลี; เจ๊ะมะลี ซูไฮมิน; รอยิง ตอยีบะห์ (YRU Journal of Science and Technology, 2018)
Traditional ladcheag is one of a popular product among Thai dessert which commonly sales across marketplaces especially during the fasting month of Muslims. However, the shelf life of product quite short. This study, aims to develops recipe and study shelf life of the traditional ladcheag. Results show that mong all 6 different formula, formula 1 which was prepared rice flour and cassava starch with (30grams) and (4 grams), ratio had highest score of all sensory aspects (p≤0.05) and overall preference of 6.16±0.83 (good). The analysis results showed pH and moisture content were not significantly different (p>0.05). Shelf-life of product packed in aluminium (AL) bag was motored over 1, 2, 3 and 4 weeks at 4 and -18 ˚C. Storage times had a significant effect on pH but not effect on moisture content (p>0.05). Storage products at -18 °C had the total number of microorganisms below the standard set in the Community Product Standards. Four weeks of storage, with a total of 5.80 × 102 CFU/g and a consumer safety standard of no more than 1x103 CFU/g.